Generation of biofuel from anaerobic digestion of Scenedesmus obliquus grown in energetic‐laden industrial wastewater: Understanding microalgae strains, co‐digestants, and digestate toxicity. Issue 2 (28th January 2022) - Mai, Andrew; Terracciano, Amalia; Abraham, Juliana; RoyChowdhury, Abhishek; Koutsospyros, Agamemnon; Su, Tsan‐Liang; Braida, Washington; Christodoulatos, Christos; Smolinski, Benjamin
Abstract: Microalgae as a substrate for anaerobic digestion (AD) offer promising outcomes over other conventional feedstocks. In this work, the generation of biofuel in the form of biogas via AD using wastewater‐grown microalgae was investigated. In particular, batch screening of different microalga strains and co‐substrates, culminated into the evaluation of biomethane potential (BMP) from AD of Scenedesmus obliquus grown in energetic‐laden wastewater through benchtop‐scale semi‐continuous reactor. Effectiveness of AD was evaluated for biogas yield, volatile solids (VS) removal, and kinetics for various microalga strains as potential substrate candidates. High carbon content co‐digestants were also investigated including return activated sludge and waste office pulped paper. At semi‐continuous scale, the specific BMPs associated with of 15, 20, and 30 days hydraulic residence times (HRT) were determined as 67.0, 86.6, and 86.3 ml CH4 /g VS (added) with average methane content of 70%. In addition, toxicological assessments showed that AD effluent was benign towards renew growth of biomass, thus showing the potential for nutrients recover.